The drying leurotus mushrooms by different types of energy - Malezhik, Ivan; Dubkovetskyy, Igor; Burlaka, Tatiana; Strelchenko, Ljudmila (My University, 2014)
The most effective method of food preservation today is dry . However , this method is also the most expensive. Therefore, the main objective of the drying process is to achieve the highest quality at a minimum cost of electricity. For dehydrated cultivated mushrooms from the energy point of view, the most appropriate drying by infrared radiation , but this method has not acquired a significant spread through thermal diffusion phenomenon. The paper studies the drying of mushrooms by three methods: convection, infrared light and a combination of these methods.
Keywords: сушіння; гриби; комбінований метод; опромінення; енергозатрати; інфрачервоне сушіння; сушка; грибы; комбинированный метод; облучение; энергозатраты; инфракрасная сушка; drying; mushrooms; combined method; irradiation; energy consumption; infrared drying; кафедра процесів і апаратів харчових виробництв